Graphene bioelectronics - Tiwari, Ashutosh, 1978- (Advanced nanomaterials series., 2017)
Graphene Bioelectronics covers the expending field of graphene biomaterials, a wide span of biotechnological breakthroughs, opportunities, possibilities and challenges. It is the first book that focuses entirely on graphene bioelectronics, covering the miniaturization of bioelectrode materials, bioelectrode interfaces, high-throughput biosensing platforms, and systemic approaches for the development of electrochemical biosensors and bioelectronics for biomedical and energy applications. The book also showcases key applications, including advanced security, forensics and environmental monitoring. Thus, the evolution of these scientific areas demands innovations in crosscutting disciplines, starting from fabrication to application. This book is an important reference resource for researchers and technologists in graphene bioelectronics-particularly those working in the area of harvest energy biotechnology-employing state-of-the-art bioelectrode materials techniques.